2015
DOI: 10.18517/ijaseit.5.6.595
|View full text |Cite
|
Sign up to set email alerts
|

The Prospect of Horticultural Organic Farming as Sustainable Agricultural Practice for Reducing Poverty: The Case in Bengkulu City, Indonesia

Abstract: Abstract-Poverty is still an insistent problem which when confronted by humanity requires a systemic, comprehensive and synchronized approach to alleviate it. The concentration of urban and rural poverty in developing countries underpins the importance of agriculture as a poverty reduction strategy since most of the poor people depend on agriculture. Thus, improving agricultural productivity, competitiveness and sustainability may reduce poverty. This study was intended to (1) find out if sustainable agricultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…For example, Adamtey et al (2016) and Bett and Ayieko (2017) in Kenya, and Yadava and Komaraiah (2020), Eyhorn et al (2018) and Mariappan and Zhou (2019) in India, documented the profitability of organic farming on rice, wheat and maize. In Indonesia, Adiprasetyo et al (2015), Fachrista et al (2019) and Widhiningsih (2020) reported similar evidence about organic vegetables. In fruits, Kleemann (2011) and Kleemann et al (2014) confirmed the economic benefits of organic certification for pineapple farmers in Ghana.…”
Section: Literature Review: Economic Performance Of Organic Farming In Developing Countriesmentioning
confidence: 76%
“…For example, Adamtey et al (2016) and Bett and Ayieko (2017) in Kenya, and Yadava and Komaraiah (2020), Eyhorn et al (2018) and Mariappan and Zhou (2019) in India, documented the profitability of organic farming on rice, wheat and maize. In Indonesia, Adiprasetyo et al (2015), Fachrista et al (2019) and Widhiningsih (2020) reported similar evidence about organic vegetables. In fruits, Kleemann (2011) and Kleemann et al (2014) confirmed the economic benefits of organic certification for pineapple farmers in Ghana.…”
Section: Literature Review: Economic Performance Of Organic Farming In Developing Countriesmentioning
confidence: 76%
“…Thus far, most studies focused on specific projects or regions and analyzed the state of the projects (e.g., Van Averbeke, 2007; Lawal and Aliu, 2012; Bendt et al, 2013; Howard Schutzbank and Riseman, 2013; Hirsch et al, 2016), the theoretical potential, virtue and needs connected with the implementation (e.g., Adiprasetyo et al, 2015; Surls et al, 2015; Prasetiyo et al, 2016), the economic viability of specific projects (e.g., Vogl et al, 2004; Adenegan et al, 2016), or the networks and organizations of community gardens (Ghose and Pettygrove, 2014; Drake and Lawson, 2015). However, Opitz et al (2017) showed that self-harvest gardens contribute to the participants’ knowledge about food, like seasonality, and also help to gain insight in agricultural production methods and farmers’ perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…So the increase in tomato weight in straw mulch with a thickness of 10% and 15% occurs because straw mulch can add adequate organic nitrogen elements to the soil. This optimal organic nitrogen makes tomato fruit growth perfect and its protein content increases [8].…”
Section: Discussionmentioning
confidence: 99%
“…Organic farming can support sustainable food security and food availability [8] like organic mulches. Organic mulches such as straw, hay, grass or leaves can provide many benefits for organic farming.…”
Section: Astesj Issn: 2415-6698mentioning
confidence: 99%